Conversations about Politics - Burton, Howard (Ideas Roadshow Collections., 2021)
Conversations About Politics is a five-part Ideas Roadshow Collection of carefully-edited Ideas Roadshow Conversations featuring leading experts with a detailed preface highlighting the connections between the different books. All five books include a detailed essay setting up the different ideas and questions for discussion at the end of each chapter. The following experts have participated in this Collection: 1. Jacques Bertrand, Professor of Political Science and Director of the Collaborative Master's Program in Contemporary East and Southeast Asian Studies at the University of Toronto;2. M.